Significados e sentidos do trabalho e identidades: aproximações e afastamentos entre “trabalho sujo” e “trabalho de prestígio” - Jefferson Rodrigues Pereira (2021)
This thesis aims to analyze possible relationships between meanings, meaningful work and identities, perceived among practitioners of "dirty" and "prestigious" work, considering their similarities, ambiguities and paradoxes. To this end, a descriptive-analytical study with a qualitative approach was developed, using the oral history method. For this purpose, 22 interviews were conducted using a semi-structured script, wherein eleven interviews were with sex workers and eleven with medical professionals. The data were recorded, transcribed and analyzed using the thematic content analysis technique. Among the main results, the differences regarding the life histories of both groups of respondents are highlighted. On the one hand, the life history of medical professionals is marked by a robust structure of family values, in which it is noticeable that the support of the family from an early age was an important aspect for the work path followed. On the other side, most sex workers' life histories are marked by poverty linked to family breakdown and violence, aspects usually assimilated as causes of their professional choices. As for the meaning of work, once again, a diametrical distance between professions was noticed. The medical profession, as an occupation, has a series of positive meanings that denote an idea of strong prestige associated with this work. Notably, its meaning is permeated by the hero's archetype, bringing ideas of nobility, altruism and distinction associated with it. For the prostitution field, their meanings are completely antagonistic to medicine field. The stain of perversion, of "dirty work" and sinfulness, as postulated by a Christian social logic that creates a set of negative meanings whose marks imply a series of harmful effects on the subject. In this way, the meaningful work attributed by the interviewees to their work ranged from their own lack of meaningful work to a high personal and social value. In addition, perceptions of meaninglessness and empowerment were also observed. The identities, in turn, emerged as a result of the interaction between the subjective unit of the individual and the context in which he is inserted, varying perceptions regarding the types and levels of recognition, appreciation and well-being of their practitioners, observing a movement tensioned by approximations and distances between the personal “I” and the professional “I”. It is important to highlight that, for the case of this study, identity is sometimes a reflection of the ambiguities, paradoxes and ambivalences of the working relationships that permeate such professions.